Tracked Foley catheter for motion compensation during fusion image-guided prostate procedures: a phantom study - Graham R. Hale; Filippo Pesapane; Sheng Xu; Ivane Bakhutashvili; Neil Glossop; Baris Turkbey; Peter A. Pinto; Bradford J. Wood (European Radiology Experimental, 2020)
Abstract Background Uncorrected patient or prostate motion may impair targeting prostate areas during fusion image-guided procedures. We evaluated if a prototype “tracked Foley catheter” (TFC) could maintain fusion image alignment after simulated organ motion. Methods A pelvic phantom model underwent magnetic resonance imaging (MRI), and the prostate was segmented. The TFC was placed in the phantom. MRI/ultrasound (US) fusion was performed. Four trials were performed varying motion and TFC presence/absence: (1) TFC/no-motion, (2) TFC/motion, (3) no-TFC/no-motion, and (4) no-TFC/motion. To quantify image alignment, screen captures generated Dice similarity coefficient (DSC) and offset distances (ODs) (maximal US-to-MRI distance between edges on fusion images). Three anatomical targets were identified for placement of a needle under fusion guidance. A computed tomography scan was used to measure system error (SE), i.e., the distance from needle tip to intended target. Results The TFC presence improved MRI/US alignment by DSC 0.88, 0.88, 0.74, and 0.61 in trials 1, 2, 3, and 4, respectively. Both OD (trial 2 versus trial 4, 4.85 ± 1.60 versus 25.29 ± 6.50 mm, p < 0.001) and SE (trial 2 versus trial 4, 6.35 ± 1.31 versus 32.16 ± 6.50 mm, p < 0.005) were significantly lower when the TFC was present after artificial motion, and significantly smaller OD when static (trial 1 versus trial 3, 4.29 ± 1.24 versus 6.42 ± 2.29 mm, p < 0.001). Conclusion TFC provided better image alignment with or without simulated motion. This may overcome system limitations, allowing for more accurate fusion image alignment during fusion-guided biopsy, ablation, or robotic prostatectomy.